2012
DOI: 10.1007/s12011-012-9433-6
|View full text |Cite
|
Sign up to set email alerts
|

Lead, Cadmium and Other Metals in Serum of Pet Dogs from an Urban Area of NW Poland

Abstract: This study was designed to evaluate the degree of exposure of pet dogs from an urban area of NW Poland to selected metals, including toxic Cd and Pb. The study was conducted on a group of 48 healthy dogs. The serum concentration of the analysed elements followed the order Fe > Al > Zn > Cu > Mn > As > Sr > Pb > Cd > Cr > Ni > V. The presence of cadmium and lead was found in all the serum samples tested. The average contents of these elements were 0.309 and 0.489 μg/mL. The factors that played the greatest role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 21 publications
0
11
0
2
Order By: Relevance
“…The investigation of chemicals present in an indoor environment has allowed the identification of the main sources of pollutants and their bioavailability has been assessed by measuring chemical residues in tissues, organs, or fluids of animals living in appropriate habitats (López-Alonso et al 2007). In this perspective, the use of pets as bi-osentinels of contamination makes it possible to determine the degree of environmental contamination and the extent of human chemical exposure, since they share the same environment as their owners and are exposed, at least in part, to the same pollutants (López-Alonso et al 2007;Tomza-Marciniak et al 2012). For example, as cats meticulously groom themselves (Fig.…”
Section: Exposure Of Pets To Indoor Contaminantsmentioning
confidence: 99%
See 1 more Smart Citation
“…The investigation of chemicals present in an indoor environment has allowed the identification of the main sources of pollutants and their bioavailability has been assessed by measuring chemical residues in tissues, organs, or fluids of animals living in appropriate habitats (López-Alonso et al 2007). In this perspective, the use of pets as bi-osentinels of contamination makes it possible to determine the degree of environmental contamination and the extent of human chemical exposure, since they share the same environment as their owners and are exposed, at least in part, to the same pollutants (López-Alonso et al 2007;Tomza-Marciniak et al 2012). For example, as cats meticulously groom themselves (Fig.…”
Section: Exposure Of Pets To Indoor Contaminantsmentioning
confidence: 99%
“…The concentrations of Pb and Cd were investigated in serum of 48 healthy pet dogs from an urban area of northwestern Poland (Tomza-Marciniak et al 2012). The mean concentrations of the analyzed metals were 0.49 and 0.31 μg/mL, respectively.…”
Section: Pets As Biosentinels Of Contamination With Metalsmentioning
confidence: 99%
“…It was revealed that the content of toxic heavy metals in animal hair is positively correlated with their level in the parenchymal organs such as liver, kidneys and skeletal muscles [Rashed, Soltan 2005, McLean et al 2009, Curi et al 2012. Pet carnivorous animals, sharing living conditions with humans, and in many cases also food, became a research object informing about the quality of environmental conditions in the human close surroundings [Kośla et al 2011b, 2013, Tomza-Marciniak et al 2012. For this reason, a domestic cat (Felis catus), the top predator of the trophic chain, became the object of interest of many research teams investigating the problem of the state of environment in the urban agglomeration.…”
Section: Streszczeniementioning
confidence: 99%
“…In order to assess various land ecosystems, numerous species of wild and domestic animals were used. The biomonitoring of the forest environment was carried out on the basis of analysis of the tissues of species representing the Cervidae family as well as European bisons, foxes and wild boars [Skibniewski et al 2010, Pilarczyk et al 2010Tomza-Marciniak et al 2012]. In relation to the rural environment, farm animals were used .…”
Section: Streszczeniementioning
confidence: 99%
“…Sua absorção depende da ingestão de cálcio, ferro, fósforo e proteínas. A meia vida do chumbo na corrente sanguínea é de 37 dias, em tecidos de 40 dias e nos ossos de 27 anos (POLÁK et al, 1996;TOMZA-MARCINIAK et al, 2012).…”
Section: Chumbo (Pb)unclassified